PENGARUH KEMUDAHAN DAN KUALITAS INFORMASI TERHADAP MINAT MAHASISWA DALAM PENGGUNAAN LAYANAN M-BANKING PADA BANK SYARIAH - Nurajizah, Nurajizah; Sari, Rika Mustika (Jurnal Al-fatih Global Mulia, 2023)
Technological developments in this rapidly growing era of globalization can attract the interest of customers who are used as supporting facilities for activities of all levels of society. One of the information technology in Islamic banking is m-banking service which is the development of the two previous forms of innovation in Islamic banking, namely SMS banking and internet banking. If interest has arisen in the prospective customer, it is hoped that the prospective customer can decide to use m-banking services. The purpose of this study was to determine the level of influence of the ease and quality of information on interest in the use of mobile banking services at Islamic banks partially or simultaneously. This study uses quantitative methods, the data used are primary and secondary data. The data collection technique used the Slovin formula sampling technique with 93 respondents. Data analysis used multiple linear regression analysis and used validity test, reliability test, classical assumption test and hypothesis test. Data processing using SPSS Version 25.0 for windows. The results of this study can be concluded that partially the convenience variable has a significant effect on student interest in using m-banking services at Islamic banks with a t-count value of 4.058 > 1.986 t table (df=90) and a sig value of 0.000 <0.05. And the information quality variable has a significant effect on student interest in using m-banking services at Islamic banks with a t-count value of 4.570 > 1986 and a sig value of 0.000 <0.05. Furthermore, the simultaneous effect with the F test shows that the ease and quality of information have a significant effect on student interest in using m-banking services at Islamic banks with a calculated F value of 122.177 > 3.10. Based on the coefficient of determination test, it shows that the influence of interest on the ease and quality of information is 73.1%, the remaining 26.9% is explained by variables outside the variables studied.